2005
DOI: 10.1111/j.1523-1755.2005.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gastric acid suppressants on cytochrome P450 3A4 and P-glycoprotein: Consequences for FK506 assimilation

Abstract: Switching treatment with cimetidine to omeprazole in renal transplant recipients is associated with a decrease of dose/weight normalized trough levels of tacrolimus. Studies in healthy volunteers suggest that this may be explained by an increase of intestinal CYP3A4 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…The strongest effects on calcineurininhibitor disposition are observed with azole antifungals, macrolide antibacterials, rifampicin, calcium channel antagonists, grapefruit juice, St John Wort and protease inhibitors. As for omeprazole, which was inconsistently found to have a pharmacokinetic interaction with tacrolimus, 41 there was no significant association here. The frequency of drug-drug interactions is high in most solid organ transplant recipients because of polypharmacy.…”
Section: Discussioncontrasting
confidence: 59%
“…The strongest effects on calcineurininhibitor disposition are observed with azole antifungals, macrolide antibacterials, rifampicin, calcium channel antagonists, grapefruit juice, St John Wort and protease inhibitors. As for omeprazole, which was inconsistently found to have a pharmacokinetic interaction with tacrolimus, 41 there was no significant association here. The frequency of drug-drug interactions is high in most solid organ transplant recipients because of polypharmacy.…”
Section: Discussioncontrasting
confidence: 59%
“…This resulted in a more than four‐fold increase of the parent/metabolite ratio for M8 (Figure 3). The effect of omeprazole on CYP3A4 has been shown to be either conflicting or demonstrating an induction [4, 22], which would ultimately result in a decrease of plasma concentrations of the parent compound and an increase of the metabolites, with a decrease of the metabolic ratio. Our findings therefore suggest a role of CYP2C19 in the metabolism of etravirine due to inhibition by omeprazole, affecting metabolite M8, rather than an effect on CYP3A4.…”
Section: Discussionmentioning
confidence: 99%
“…No major interaction of omeprazole with the CYP3A4 substrate ciclosporin was described previously [20]. In another study, a 40% reduction of the metabolite excretion of the CYP3A probe dapsone was shown, although a study in renal transplant patients has demonstrated a decrease of tacrolimus exposure when co‐administered with omeprazole, attributed to the induction of intestinal CYP3A4 activity [21, 22].…”
Section: Introductionmentioning
confidence: 97%
“…To avoid this complication, we tested our hypothesis in a proofof-concept study using both cimetidine and ranitidine. Although cimetidine is a strong inhibitor of P450 enzymes in both humans and animals, ranitidine is considered a weak inhibitor with an affinity for P450 that is 10 times lower than that of cimetidine [21][22][23]. Therefore, any differences between cimetidine and ranitidine in their effects on IR injury would be due, most likely, to P450 inhibition by cimetidine.…”
Section: Introductionmentioning
confidence: 98%